2020
DOI: 10.36380/scil.2020.wvj10
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Stillbirth in Swine Farms in Vietnam.

Abstract: Stillbirth in pig has been studied worldwide, but, its situation in Vietnam has never been reported. Therefore, present study aimed to investigate effects of herd, parity, gestation length, birth litter size and farrowing duration on stillbirth at sow level in swine farms in Vietnam. Data was collected from 1174 litters of 1174 Landrace x Yorkshire crossbred sows in 16 farms in the North of Vietnam. Potential risk factors for stillbirth were identified by using logistic regression. The incidence of stillbirth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
1
1
1
Order By: Relevance
“…The stillbirth rate (8.1%) found in this study is higher than that previously reported by many other authors [14,[17][18][19][20]. The proportion of litters having stillbirth(s) (59.5%) was also higher than that in any previously published articles [3,5,17,21].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The stillbirth rate (8.1%) found in this study is higher than that previously reported by many other authors [14,[17][18][19][20]. The proportion of litters having stillbirth(s) (59.5%) was also higher than that in any previously published articles [3,5,17,21].…”
Section: Discussioncontrasting
confidence: 75%
“…Some authors did not detect any effect of GL on stillbirth [29]. In contrast, the negative association between short GL and stillbirth has been reported [17]. Piglets born from a short GL associated with immaturity [28] and, therefore, acquired higher risk of being stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Збільшення кількості мертвонароджених у гнізді може бути пов'язане із багатьма факторами, наприклад, властивостями свиноматки, а саме, наявністю мертвонароджених або поросят із низькою життєздатністю в попередніх опоросах, збільшенням тривалості опоросу, надмірною живою масою свиноматки, зниженням концентрації гемоглобіну в крові, збільшенням номера опоросу, зростанням кількості поросят у гнізді та розміру гнізда за попереднього опоросу тощо. Крім того, певні фактори, що характеризують порося, можуть спровокувати його смерть до, під час або відразу після народження; це: пізніший номер у порядку народження, низька маса при народженні або пошкодження пуповини (Zaleski & Hacker, 1993;Kirkden et al, 2013;Vanderhaeghe et al, 2013;Muñoz et al, 2017;Rangstrup-Christensen et al, 2017;Nam & Sukon, 2020;Schild et al, 2020). У цілому, кількість (та частка) мертвонароджених поросят у гнізді збільшується з віком (номером опоросу) свиноматок та зі збільшенням кількості поросят у гнізді при народженні (Fraser et al, 1997).…”
Section: вступunclassified